Integrating Good Governance and Digitalisation: A New Breakthrough in the Special Economic Zone of Singhasari - Cahyandari, Dewi; Susilo, Edi; Hadiyantina, Shinta; Prasetyo, Ngesti D.; Supriyadi, Aditya Prastian; Liemanto, Airin; Arifien, Zainal; Supriyadi, Rizki Febrianto; Lestari, Diah Charisma (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2022)
Special Economic Zones (SEZs) aim to boost the economy of a region or even a country. In Indonesia, as of 2022, eighteen regions belonged to SEZs, and Singhasari is among those regions—the only SEZ with a digital economic concept. In its implementation, a Good Governance concept is needed to allow for the organisation of management and the achievement of the goals of the development of the SEZ. Concepts such as Community Participation, Stakeholder Involvement, and Local Ownership will be discussed in this research. On the other hand, technology can be utilised to give value to SEZ. The digitalisation of the SEZ can be used in the implementation of Good Governance concepts as well as attracting people and investors to participate. The concept of digitizing the SEZ Singhasari area utilising Augmented Reality and Virtual Reality can be used to introduce the SEZ of Singhasari. Besides, there are also other features such as legal materials underpinning the development of SEZ Singhasari. This study used the principle of Good Governance that underlies SEZ governance. Meanwhile, the concept of digitalisation with the addition of augmented and virtual reality will be used as one of the breakthroughs to harmonize development in the current technological era. Keywords: Special Economic Zone, Singhasari, Digitalisation, Good Governance.